2011
DOI: 10.1016/j.ajpath.2011.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of the Imprinted DLK1-MEG3 Locus in Human Clinically Nonfunctioning Pituitary Adenomas

Abstract: DLK1-MEG3is an imprinted locus consisting of multiple maternally expressed noncoding RNA genes and paternally expressed protein-coding genes. The expression of maternally expressed gene 3 (MEG3) is selectively lost in clinically nonfunctioning adenomas (NFAs) of gonadotroph origin; however, expression status of other genes at this locus in human pituitary adenomas has not previously been reported. Using quantitative real-time RT-PCR, we evaluated expression of 24 genes from the DLK1-MEG3 locus in 44 human pitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
70
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 49 publications
9
70
0
4
Order By: Relevance
“…In agreement with our data, miR-410 was previously found downregulated in NFPAs (nonfunctioning pituitary adenomas) adenomas, within the DLK1-MEG3 locus, which contains one of the largest miRNA clusters in humans, and its expression has been correlated with MEG3 (maternally expressed gene 3), a maternally expressed noncoding RNA frequently lost in clinically NFPAs of gonadotroph origin. 24 Moreover, other previous studies have evidenced a tumor suppressor activity for this miRNA. Indeed, miR-410 has been found downregulated gliomas 19 and gastric carcinomas 25 where lower miRNA-410 expression levels significantly correlated with the presence of lymph-node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our data, miR-410 was previously found downregulated in NFPAs (nonfunctioning pituitary adenomas) adenomas, within the DLK1-MEG3 locus, which contains one of the largest miRNA clusters in humans, and its expression has been correlated with MEG3 (maternally expressed gene 3), a maternally expressed noncoding RNA frequently lost in clinically NFPAs of gonadotroph origin. 24 Moreover, other previous studies have evidenced a tumor suppressor activity for this miRNA. Indeed, miR-410 has been found downregulated gliomas 19 and gastric carcinomas 25 where lower miRNA-410 expression levels significantly correlated with the presence of lymph-node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Nor ma lia me hi po fi zës au diny je jo eks pre si ja yra ið reikð ta, o ser gant ne funk cio nuo janèia HA, ji ið nyks ta ar ba la bai su ma þë ja [23,29,36]. At liktuo se ty ri muo se, ieð kant ðio reið ki nio prie þas ties, bu vo atmes tos de le ci jos ir ki tos mu ta ci jos, ta èiau ras tas pa di dë jaes dvie jø re gio nø, IG-DMR ir MEG3-DMR, me ti li ni mas [37].…”
Section: Sporadinës Haunclassified
“…They act as tumour suppressors or oncogenes, depending on the function of the targeted genes, and seem to be involved in the regulation of many steps of tumour progression. Results from studies comparing pituitary tumours to normal pituitary (95,96,97,98,99,100,101,102,103,104,105,106,107,108) suggest that miRNA deregulation may play a key role in pituitary tumourigenesis. Indeed, D'Angelo et al (101) identified a set of miRNAs, including miR-34b, miR-326, miR-432, miR-548c-3p, miR-570 and miR-603, that were drastically and consistently down-regulated in GH adenomas and demonstrated that these miRNAs target genes with critical roles in pituitary tumourigenesis, such as high-mobility group A1 (HMGA1), HMGA2 and E2F1.…”
Section: Epigenetic Regulation By Microrna Expression Studiesmentioning
confidence: 99%